Respuesta :
Answer:
The 12th term in the sequence is b(12)= -26
Step-by-step explanation:
For the 12th term, that means we need to find what the value of b is when n=12
To find b:
- Substitute all 'n' with 12 (since its the 12th term)
b(n)= -4-2(n-1)
b(12)= -4-2(12-1)
- Solve the equation in order of BEDMAS (aka PEDMAS)
b(12)= -4-2(11)
= -4- (2*11)
= -4-(22)
= -26
The 12th term in the sequence is b(12)= -26
ANSWER: -26
WHY:
B(12)= -4-2(12-1)
-4-2(11)
-4-22
-26
MARK ME BRAINLIEST PLEASE
WHY:
B(12)= -4-2(12-1)
-4-2(11)
-4-22
-26
MARK ME BRAINLIEST PLEASE